2017
DOI: 10.15376/biores.12.4.9130-9142
|View full text |Cite
|
Sign up to set email alerts
|

Use of bacterial cellulose in degraded paper restoration: Effect on visual appearance of printed paper

Abstract: One of the most common methods used to reinforce damaged paper is to apply a lining, using Japanese paper (JP). The reinforcing material must consolidate the paper without modifying its visual appearance. The unique properties of bacterial cellulose (BC) suggest that it could be efficiently used to reinforce degraded paper documents. The changes in the visual appearances of the printed commercial papers lined with BC and JP were examined in this study. Four commercial papers, coated and uncoated, were printed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…One of the methods used by conservators to restore damaged paper is the application of a reinforcing layer on the paper surface, known as lining, which allows the loss of mechanical resistance to be recovered (Bansa and Ishii, 1997). The material typically used for this purpose is Japanese Paper which provides a high resistance, but it is not entirely satisfactory for all documents because the sheets are not very homogeneous (Gómez et al, 2017). Nanocelluloses have emerged as a novel and innovative approach in the conservation and restoration of paper documents because they can solve many challenges such as structural weaknesses, pH instability, moisture exposure and damage repair.…”
Section: Nanocelluloses In Historical Documentsmentioning
confidence: 99%
“…One of the methods used by conservators to restore damaged paper is the application of a reinforcing layer on the paper surface, known as lining, which allows the loss of mechanical resistance to be recovered (Bansa and Ishii, 1997). The material typically used for this purpose is Japanese Paper which provides a high resistance, but it is not entirely satisfactory for all documents because the sheets are not very homogeneous (Gómez et al, 2017). Nanocelluloses have emerged as a novel and innovative approach in the conservation and restoration of paper documents because they can solve many challenges such as structural weaknesses, pH instability, moisture exposure and damage repair.…”
Section: Nanocelluloses In Historical Documentsmentioning
confidence: 99%
“…However, with these treatments, the damaged areas of paper were consolidated, as visible in Figure 9, and the results of the application of BNC and CNF suspensions were comparable with the adhesive consolidation; they did not alter the visual appearance of ancient papers, even in the long term, and permitted an innovative approach for paper stabilization. Other research works, such as those reported by Gomez et al [96] and Santos et al [97,98], showed the use of bacterial nanocellulose (BNC) for the paper reinforcement as a replacement of the usual Japanese paper coating method, obtaining excellent results in terms of the minimum thickness of the coating and better legibility of the characters after processing, although with a slight yellowing of the surface due to the aging process. Moreover, the treatment with BNC decreased the wettability due to the reduction in air permeance, an important aspect that prevents the formation of mold.…”
Section: Historical Papersmentioning
confidence: 99%
“…Bergamonti et al [16] proposed a new treatment for the conservation and consolidation of ancient papers based on the use of cellulose nanocrystals (CNCs) with the addition of silver (Ag) nanoparticles in order to obtain both a consolidating action due to nanocellulose and biocidal activity by Ag nanoparticles (Figure 10). Other research works, such as those reported by Gomez et al [96] and Santos et al [97,98], showed the use of bacterial nanocellulose (BNC) for the paper reinforcement as a replacement of the usual Japanese paper coating method, obtaining excellent results in terms of the minimum thickness of the coating and better legibility of the characters after processing, although with a slight yellowing of the surface due to the aging process. Moreover, the treatment with BNC decreased the wettability due to the reduction in air permeance, an important aspect that prevents the formation of mold.…”
Section: Historical Papersmentioning
confidence: 99%